Implementation of image super-resolution on rasberry Pi / \c Comfort Abiodun Iyanda. - Iyanda, Comfort Abiodun (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2017)
The main aim of this research is the implementation ofSR algorithm on a Raspberry Pi platform while investigating the performance accordingly. This includes ; to develop and implement imageSR algorithm based on IBP using MATLAB and Raspberry Pi 2 B+respectively ; to validate the performance of image SRalgorithm onRaspberry pi 2 B+ in comparison with General Purpose Computer using image metrics including PSNR, and MSE.